NEUTRINO IN GRAVITATIONAL FIELD - Plyatsko, R. M.; Fenyk, M. T. (Одеські астрономічні публікації, 2014)
The spin-gravity coupling for highly relativistic fermions according to the classical Mathisson-Papapetrou and quantum Dirac equations is considered. It is stressed that the behavior of fermions in the highly relativistic regime in the gravitational field is significantly different as compare to usual situations. Possible corrections to the known general relativistic Dirac equation for more adequate description of fermions in strong gravitational fields are discussed. Some numerical estimates for neutrinos with nonzero mass that is interesting in astrophysicsare presented.